2009
DOI: 10.1111/j.1542-474x.2009.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of P‐Wave Morphology in Healthy Individuals: A 3‐Year Follow‐Up Study

Abstract: In the majority of healthy subjects, P-wave morphology is stable at 3-year FU. Subtle morphological changes, observed principally in Lead Z, suggest variation of interatrial conduction. These changes could not be detected by measuring conventional PWD that remained unchanged in the total population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Another interesting result of this study was that the P wave from healthy subjects did not show a substantial variability over time. This finding is in line with previous studies which demonstrated that P wave morphology was stable over a long time period in the majority of healthy subjects . In fact, this information provided to be clinically useful to discern between healthy subjects and PAF patients in normal sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting result of this study was that the P wave from healthy subjects did not show a substantial variability over time. This finding is in line with previous studies which demonstrated that P wave morphology was stable over a long time period in the majority of healthy subjects . In fact, this information provided to be clinically useful to discern between healthy subjects and PAF patients in normal sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…Automatic techniques are based on signal processing algorithms, by which reliable and reproducible measures of P-wave features can be obtained, such as quantification of P-wave duration and objective measures of P-wave morphology; signal processing tools also allow us to obtain the quantification of other P-wave features not distinguishable by visual inspection (e.g. the root mean square of the last 20 ms of the P-wave, P-wave energy by wavelet analysis, etc (Vassilikos et al 2011, Lim et al 2010, Kaykha et al 2010, Diery et al 2011, Havmöller et al 2009, Ishida et al 2010).…”
Section: Introductionmentioning
confidence: 99%